Edukasi Senam Lantai dalam Rangka Meningkatkan Keterampilan Gerak di SMA Negeri 1 Paguyaman - Datau, Suriyadi; Tumaloto, Ella H; Ruslan, Ruslan; Mile, Sarjan; Kadir, Sulasikin Sahdi; Ilham, Al; Sidu, Sartin (-, 2025)
This community service activity aims to provide floor gymnastics education to improve students' movement skills at SMA Negeri 1 Paguyaman. Floor gymnastics is important in physical education learning because it trains strength, balance, coordination, and flexibility of the body. Based on initial observations, the majority of students experienced difficulties in performing basic movements due to a lack of technical understanding and limited practice. This activity was carried out with a participatory educational approach through four stages: program socialization, delivery of theoretical material, demonstration of basic techniques (forward rolls, backward rolls, candle poses, and simple handstands), and evaluation through direct observation and feedback. The results of the activity showed significant improvements, where 85% of students were able to perform forward rolls and candle poses correctly, an increase from the previous 40%. Students also showed enthusiasm and active participation during the training. Physical Education teachers are committed to continuing floor gymnastics practices as part of continuous learning at the school.